2020
DOI: 10.1039/c9tc06630f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast, self-powered and charge-transport-layer-free photodetectors based on high-quality evaporated CsPbBr3 perovskites for applications in optical communication

Abstract: Ultrafast and self-powered photodetectors based on high-quality evaporated CsPbBr3 perovskites for applications in optical communication are demonstrated. The photodetectors achieve an ultrafast response time of 3.8 μs and on/off ratio of 3.5 × 104.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 67 publications
2
36
0
Order By: Relevance
“…In addition, the response and recovery times are estimated to be 5 and 6 μs (defined as the time interval for the values to reach 90% and decrease to 10 % of the maximum amplitude, respectively). Notably, the response time and recovery times are comparable to those of outstanding fibre-shaped perovskite photodetectors and are also sufficient for text and audio transmission in optical communication systems 39,40 . As illustrated in Fig.…”
Section: Full-duplex Light Communication Based On the El-pd Bifunctiomentioning
confidence: 84%
“…In addition, the response and recovery times are estimated to be 5 and 6 μs (defined as the time interval for the values to reach 90% and decrease to 10 % of the maximum amplitude, respectively). Notably, the response time and recovery times are comparable to those of outstanding fibre-shaped perovskite photodetectors and are also sufficient for text and audio transmission in optical communication systems 39,40 . As illustrated in Fig.…”
Section: Full-duplex Light Communication Based On the El-pd Bifunctiomentioning
confidence: 84%
“…Although several reports on the sequential deposition of CsPbBr 3 perovskites can be found out in the literature, there have been limited reports on the fabrication of CsPbBr 3 photodetectors via sequential evaporation method. Liu et al [ 173 ] developed a sequential evaporation to prepare dense CsPbBr 3 photosensitive layer, which is well regulated than the conventional solution‐processing process. It was revealed that the evaporated films exhibited uniform coverage, higher crystallinity, phase purity, and light harvesting proficiency than the traditional solution‐processed counterparts.…”
Section: Dual‐source Evaporation Depositionmentioning
confidence: 99%
“…It is worth mentioning that a vertical HTL-free architecture was adopted for the fabrication of the ML-perovskite pressure sensor to simplify the device architecture and reduce the fabrication cost. Although the utilization of HTL in perovskite photodetectors have been demonstrated to be effective in increasing the photodetector performance, most HTL materials, such as 2,2′,7,7′-Tetrakis[N, N-di(4-Methoxyphenyl) Amino]-9,9′-spirobifluorene (Spiro-OMETAD), are expensive, which significantly increases the fabrication costs of the device [33][34][35]. The device fabrication was completed by thermal evaporation of the Au electrode on the perovskite layer [36][37][38].…”
Section: Device Architecturementioning
confidence: 99%